2017
DOI: 10.1039/c7cc01997a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced catalytic performance of a PdO catalyst prepared via a two-step method of in situ reduction–oxidation

Abstract: A supported PdO nanocatalyst prepared by a facile in situ reduction process followed by an oxidation step showed significantly enhanced activity for the removal of pollutants from natural gas vehicles. The excellent catalytic performance is mainly due to high dispersion of the uniform PdO nanoparticles generated during the novel two-step method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
4
13
0
Order By: Relevance
“…XRD analysis of the most efficient catalyst (1#, 5% Pd/C from Strem Chemicals) (Figure A) obtained diffraction peaks at 2θ of 33.3, 34.4, 42.9, and 55.3° that are assigned to the (002), (101), (110), and (112) facets of tetragonal PdO (powder diffraction file, PDF No. 88-2434), respectively. , The existence of palladium was confirmed by the peaks at 2θ of 40.1, 46.7, and 68.1° that correspond to the (111), (200), and (220) planes of cubic Pd (PDF No. 05-0681), respectively. While the XRD pattern for the two lower quality catalysts (Figure A, 2# and 3#) show clear peaks at 33.3, 34.4, 42.9, and 55.3° for crystalline tetragonal PdO, matching well with PDF No.…”
Section: Results and Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…XRD analysis of the most efficient catalyst (1#, 5% Pd/C from Strem Chemicals) (Figure A) obtained diffraction peaks at 2θ of 33.3, 34.4, 42.9, and 55.3° that are assigned to the (002), (101), (110), and (112) facets of tetragonal PdO (powder diffraction file, PDF No. 88-2434), respectively. , The existence of palladium was confirmed by the peaks at 2θ of 40.1, 46.7, and 68.1° that correspond to the (111), (200), and (220) planes of cubic Pd (PDF No. 05-0681), respectively. While the XRD pattern for the two lower quality catalysts (Figure A, 2# and 3#) show clear peaks at 33.3, 34.4, 42.9, and 55.3° for crystalline tetragonal PdO, matching well with PDF No.…”
Section: Results and Discussionsupporting
confidence: 53%
“…88-2434), respectively. 12,13 The existence of palladium was confirmed by the peaks at 2θ of 40.1, 46.7, and 68.1°that correspond to the (111), (200), and (220) planes of cubic Pd (PDF No. 05-0681), respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…X-ray diffraction (XRD) analysis of the 5% Pd/C from Strem Chemicals ( Figure 1A) obtained diffraction peaks of at 2θ of 33.3°, 34.4°,42.9 and 55.3° are assigned to the (002), (101), (110) and (112) facets of tetragonal PdO (powder diffraction file, PDF No. 88-2434), 6,7 the existence of palladium was confirmed by the peaks at 2θ of 40.1°, 46.7° and 68.1°, which are correspondent to the (111), (200) and (220) planes of cubic Pd (PDF No. 05-0681) respectively.…”
Section: Palladium Catalyst Analysismentioning
confidence: 94%
“…In recent years, the liquid-phase reduction-impregnation method has been widely used to prepare metal nanoparticles and metal particles with nano-sized supported catalysts, and the commonly used reductants include formaldehyde, ethanol, ethylene glycol, glycerol, ascorbic acid, , and NaBH 4 . Chen et al synthesized Pt/Al 2 O 3 catalysts with different Pt particle sizes by the modified ethylene glycol reduction approach and used it for benzene oxidation, and they found that the Pt/Al 2 O 3 catalyst with 1.2 nm Pt size showed the best catalytic oxidation activity of benzene at 145 °C.…”
Section: Introductionmentioning
confidence: 99%